Design and Testing of 3D-Printed Stackable Plant-Microbial Fuel Cells for Field Applications - Glenn Paula P Constantino; Justine Mae C. Dolot; Kristopher Ray Simbulan Pamintuan (International Journal of Renewable Energy Development, 2023)
The prevalence of non-renewable energy has always been a problem for the environment that needs a long-term solution. Plant-Microbial Fuel Cells (PMFCs) are promising bioelectrochemical systems that can utilize plant rhizodeposition to generate clean electricity on-site, without harming the plants, paving the way for simultaneous agriculture and power generation. However, one of the biggest hurdles in large-scale PMFC application is the diffused nature of power generation without a clear path to consolidate or amplify the small power of individual cells. In this study, stacking configurations of 3D-printed PMFCs are investigated to determine the amplification potential of bioelectricity. The PMFCs designed in this study are made of 3D-printed electrodes, printed from 1.75 mm Proto-pasta (ProtoPlant, USA) conductive PLA filament, and a terracotta membrane acting as the separator. Six cells were constructed with the electrodes designed to tightly fit with the ceramic separator when assembled. An agriculturally important plant (S. Melongena) was utilized as the model plant for testing purposes. Stacking of cells in series had resulted in severe voltage loss while stacking of cells in parallel preserved the voltage and current of the cells. Cumulative stacking verified the increasing voltage losses as more cells are connected in series, while voltage and current were generally supported well as more cells were connected in parallel. Combination stacks were also investigated, but while 2 sets of 3 cells in parallel stacked in series generated proportionately larger power and power density compared to individual cells, the drop in current density suggests that pure parallel stacks are still more attractive for scaling up, at least for the proposed stake design in this study. The results of this study indicated that the scale up of PMFC technology is possible in field applications to continuously generate electricity while growing edible plants.